2011
DOI: 10.4102/sajems.v14i4.134
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the price elasticity for demand for electricity by sector in South Africa

Abstract: This paper analyses electricity consumption patterns in South Africa in an attempt to understand and identify the roots of the current electricity crisis. This is done by investigating various economic sectors’ responses to price changes using panel data for the period 1993–2004. Positive and statistically significant price elasticities over this period were found for the transport (rail) and commercial sectors while there are positive, but small and statistically insignificant responses to price changes in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 24 publications
3
19
0
Order By: Relevance
“…For example, both Al-Sahlawi (1999) and Eltony and Mohammad (1993) found that income elasticity of industrial electricity consumption was inelastic for Saudi Arabia. An inelastic income elasticity is also supported by the other industrial electricity demand studies conducted for other economies, such as Jamil and Ahmad (2010), Dilaver andHunt (2011), Inglesi-Lotz andBlignaut (2011), and Arisoy and Ozturk (2014). Our explanation for the inelastic income effect is the subsidized industrial electricity price, as discussed.…”
Section: Econometric Findingssupporting
confidence: 81%
“…For example, both Al-Sahlawi (1999) and Eltony and Mohammad (1993) found that income elasticity of industrial electricity consumption was inelastic for Saudi Arabia. An inelastic income elasticity is also supported by the other industrial electricity demand studies conducted for other economies, such as Jamil and Ahmad (2010), Dilaver andHunt (2011), Inglesi-Lotz andBlignaut (2011), and Arisoy and Ozturk (2014). Our explanation for the inelastic income effect is the subsidized industrial electricity price, as discussed.…”
Section: Econometric Findingssupporting
confidence: 81%
“…DME does not conduct any independent surveys or regular data audits but relies on the credibility of the data providers and the National Energy Regulator (NERSA). A quality control process is in place involving a manual data check querying when inconsistencies are observed and a subsequent review process with major local and international organisations such as the International Energy Agency (IEA) [37].…”
Section: Datamentioning
confidence: 99%
“…All the studies investigating the causal relationship between electricity (energy) growth and economic growth in the country (Wolde‐Rufael, , ; Odhiambo, ; Eggoh et al ., ; Al‐mulali and Sab, ; Kahsai et al ., ; Dlamini et al ., , forthcoming) assumed a linear relationship between the two. Looking at the various factors that influence the energy or electricity consumption in the country, almost all studies agreed that income and price are the main determinants but again in a linear format (Louw et al ., ; Ziramba, ; Amusa et al ., ; Inglesi, ; Inglesi and Pouris, ; Inglesi‐Lotz and Blignaut, ; Senatla, ; Inglesi‐Lotz et al ., ). Inglesi‐Lotz (, ) looked the time‐varying price elasticities of aggregate and industrial electricity consumption in South Africa, taking thus into account possible differences in the behaviour of consumers from one year to another.…”
Section: The South African Energy Marketmentioning
confidence: 99%